2020
DOI: 10.1111/jbi.14041
|View full text |Cite
|
Sign up to set email alerts
|

A Holocene history of monkey puzzle tree (pehuén) in northernmost Patagonia

Abstract: Aim Although it is established that climate and fire have greatly influenced the long‐term ecosystem dynamics of Patagonia south of 40°S, the environmental history from northernmost Patagonia (37–40°S), where endemic and endangered monkey puzzle tree (Araucaria araucana) occurs, is poorly known. Here we ask: (a) What is the Holocene vegetation and fire history at the north‐eastern extent of A. araucana forest? (b) How have climate and humans influenced the past distribution of A. araucana? Location Northernmos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 53 publications
0
7
1
Order By: Relevance
“…A recent pollen record from Lake Cilantro (Dickson et al, 2020) shows similar patterns as those observed in Lake Relem, neither changes in pollen relative abundance after small tephra layers nor changes in PAR after So-A eruption. Although not a generalised pattern, Dickson et al (2020), Moreno-Gonzalez et al (2021 and Nanavati et al, (2020) showed that pollen abundance in areas nearby the current ecotone have been slightly increasing for the last˜4 ka despite of the influence of several volcanic eruptions. Further palaeoecological studies need to be done to understand the role of past volcanic eruptions in determining current diversity patterns in Araucaria forest and that can be used in the conservation of certain threatened species in the Valdivian Temperate Rainforest hotspot.…”
Section: Discussionmentioning
confidence: 87%
“…A recent pollen record from Lake Cilantro (Dickson et al, 2020) shows similar patterns as those observed in Lake Relem, neither changes in pollen relative abundance after small tephra layers nor changes in PAR after So-A eruption. Although not a generalised pattern, Dickson et al (2020), Moreno-Gonzalez et al (2021 and Nanavati et al, (2020) showed that pollen abundance in areas nearby the current ecotone have been slightly increasing for the last˜4 ka despite of the influence of several volcanic eruptions. Further palaeoecological studies need to be done to understand the role of past volcanic eruptions in determining current diversity patterns in Araucaria forest and that can be used in the conservation of certain threatened species in the Valdivian Temperate Rainforest hotspot.…”
Section: Discussionmentioning
confidence: 87%
“…The pollen and charcoal data from Laguna Portezuelo indicate the presence of an open, forest–steppe ecotonal landscape and steady fire activity through much of the Holocene ( Fig. 3 B ) ( 15 ). Rising pollen percentages of Nothofagus after 6590 cal y BP suggest more forest cover and increased moisture in the late Holocene.…”
Section: Discussionmentioning
confidence: 99%
“…We suggest that fire activity after ∼1580 CE (370 cal y BP) was amplified by climate-driven increases in fuel load during the LIA and in anthropogenic ignitions. A. araucana was of great cultural and resource significance to Mapuche and Pehuenche peoples ( 53 ), and evidence of its increase and more fires after ∼1580 CE (370 cal y BP) suggests local silvicultural management through deliberate burning ( 15 ). Tree-ring records near Laguna Portezuelo also indicate frequent fires at ∼6-y intervals during Mapuche–Pehuenche occupation ( 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…The authors recorded neither changes in pollen relative abundance after small tephra layers nor changes in PAR after So‐A eruption. Instead, Dickson et al ( 2020 ), Moreno‐Gonzalez et al ( 2021 ), and Nanavati et al ( 2020 ) showed that pollen abundance in areas near the current ecotone has been slightly increasing for the last ~4 ka despite the influence of several volcanic eruptions. Further palaeoecological studies need to be done to understand the role of past volcanic eruptions in determining current diversity patterns in Araucaria forest and that can be used in the conservation of certain threatened species in the Valdivian Temperate Rainforest hotspot.…”
Section: Discussionmentioning
confidence: 99%